2018
DOI: 10.1088/1361-665x/aacdc6
|View full text |Cite
|
Sign up to set email alerts
|

Segmented impact-type piezoelectric energy harvester for self-start impedance matching circuit

Abstract: This paper proposes a segmented impact-type piezoelectric energy harvester (PEH) for self-start impedance matching circuit. Generally, an oscillator in an impedance matching circuit requires a separate power supply. Considering randomness and intermittence of wind energy, a design of a smart power controller is essential for efficient and timely power supply to the oscillator. The proposed segmented impact-type PEH is designed to achieve an ultra-low power consumption for an impedance matching circuit operatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…The resonant frequency-based cantilever design of a piezoelectric vibration energy harvester gives better output at its resonant frequency, compared to the impact type device [17]. Hence, methods to tune its natural frequency to different values matching with the ambient frequency open up a wide range of applications.…”
Section: Design Of a Novel Tunable Piezoelectric Vibration Energy Harmentioning
confidence: 99%
“…The resonant frequency-based cantilever design of a piezoelectric vibration energy harvester gives better output at its resonant frequency, compared to the impact type device [17]. Hence, methods to tune its natural frequency to different values matching with the ambient frequency open up a wide range of applications.…”
Section: Design Of a Novel Tunable Piezoelectric Vibration Energy Harmentioning
confidence: 99%
“…The regular contact between the free end of the piezoelectric vibrator and the rotor blades is utilized to drive the vibrational deformation of the piezoelectric vibrator and output electrical energy. Jung et al [20,21] suggested a breeze-impact PEH. Vibration is produced when the piezoelectric cantilever beam collides with the wind turbine.…”
Section: Introductionmentioning
confidence: 99%
“…There are three typical methods to develop numerical models for PE harvesters: the finite element method (FEM) [29,30], analytical methods [1,[31][32][33], and the classical Ritz method (CRM) [1,[34][35][36][37][38][39]. Each method has its advantages and disadvantages.…”
Section: Introductionmentioning
confidence: 99%